Decompressive craniectomy for malignant middle cerebral artery infarction in a 16-year old boy: a case report. (December 2016) - Lammy, Simon; Fivey, Paul; Sangra, Meharpal
Abstract Background Cryptogenic stroke frequently occurs in younger patients and has a high risk of recurrence. Consequently, secondary prevention is often suboptimal as there is no known risk factor to target. This case demonstrates an unexpected finding of middle cerebral artery infarction and extensive malignant transformation in a 16-year-old boy more than a day post-admission. The lack of a proven culprit lesion makes this case even more intriguing and subsequently raises questions of cryptogenic mechanisms in the context of unrelated trauma. Case presentation A 16-year-old white boy had been stabbed in his chest but had a Glasgow Coma Scale score of 15. Over a day later he developed sudden signs and symptoms consistent with a neurological event of unknown etiology. Computed tomography demonstrated significant cerebral edema but was equivocal in its list of differentials. A computed tomography scan of his chest demonstrated no cardiac wall or vascular injury and he was transferred to our neurosurgical unit for intracranial pressure monitoring. A computed tomography angiogram revealed an unexpected finding of malignant middle cerebral artery infarction. Failure to medically manage his intracranial pressure resulted in a decompressive craniectomy less than 12-hours postictus. Despite extensive diagnostic investigations no culprit lesion was identified and no patent foramen ovale found. Since discharge he has returned to full functional status. He was the youngest patient (mean age of 43 years) out of a 10-year institutional retrospective on decompressive craniectomies for malignant middle cerebral artery infarction (n  = 40) and had the singularly best Glasgow Outcome Scale score of 5. Conclusions This case highlights the preponderance of cryptogenic stroke in younger patients and its etiological elusiveness. It further demonstrates that age is predictive in terms of survival and functional outcome in the context of malignant middle cerebral artery infarction.